1982
DOI: 10.1093/oxfordjournals.aje.a113385
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Pulmonary Function as a Risk Factor for Mortality

Abstract: Prospective follow-up information obtained between 1976 and 1981 on mortality among 2539 individuals showed that pulmonary function impairment is a risk factor for short-term mortality, even when risk factors such as age, sex, and smoking are considered. Predicted risk curves for impaired individuals (those with forced expiratory volume in one second less than 68% of forced vital capacity) are consistently higher among all race-sex categories over all ages. Survival analysis using the proportional hazards mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(66 citation statements)
references
References 0 publications
6
59
1
Order By: Relevance
“…Several studies have found an association between impaired lung function and death (32)(33)(34). We found that a 10% decrease in FEV 1 was associated with a 12% increase in all-cause mortality, a figure very similar to the 11-15% increase found in the general population (14,35,36), including a report from Busselton (15).…”
Section: Baseline Patient Characteristicssupporting
confidence: 82%
“…Several studies have found an association between impaired lung function and death (32)(33)(34). We found that a 10% decrease in FEV 1 was associated with a 12% increase in all-cause mortality, a figure very similar to the 11-15% increase found in the general population (14,35,36), including a report from Busselton (15).…”
Section: Baseline Patient Characteristicssupporting
confidence: 82%
“…Similar associations were found in the secondary analyses looking at individual positions within each gene (Table S4), but only some of the positions showed significant associations: mortality, [13][14][15] though the causal pathways are poorly understood. 13,16 Faster lung function decline has been associated with increased risks of hospitalizations related to chronic obstructive pulmonary disease (COPD), 17 which is a leading cause of mortality in all countries.…”
Section: Gene Promoter Methylation Is Associated With Lung Function Isupporting
confidence: 72%
“…42) FEV 1 and VC are the tests most widely used for the diagnosis of impaired pulmonary function, and are considered independent risk indicators for cardiovascular diseases. 43) In our study the inverse relationship between FEV 1 or VC and CHF mortality persisted after adjustment for age; according to Kannel, et al 44) reduced pulmonary function therefore independently predicts CHF death. The mechanism of this association is not well established.…”
Section: )supporting
confidence: 60%